Guidelines for the Development of Social Media Marketing Strategies (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This academic article aims to propose an effective approach to developing social media marketing strategies by integrating the RACE Framework, Customer Journey, and S.M.A.R.T Goals. The integration of these concepts enables the design of strategies that comprehensively align with consumer behavior in the digital age. The article outlines a planning process that includes goal setting, platform selection, content creation, engagement building, and performance measurement using key performance indicators such as Engagement Rate, Conversion Rate, and Retention Rate. Additionally, real-world case studies are provided to demonstrate the practical application of the proposed framework. The outcome of this article is a structured strategic model that helps marketers and entrepreneurs evaluate and improve their digital marketing strategies with greater precision. It minimizes misalignment in platform selection and goal setting, and provides a flexible model adaptable to various business types and market contexts. This article serves as a practical tool to enhance strategic understanding and skills for those aiming to gain competitive advantages in the rapidly evolving landscape of digital marketing.